(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis analyzes the economic management system of non-state higher education institutions, its core principles, mechanisms for ensuring financial sustainability, and the specific characteristics observed in practical activities. In modern conditions, non-state higher education institutions are emerging as important players in the education services market. They face the dual task of not only delivering quality education but also establishing an effective system of economic management. The study examines financial resource planning, revenue and expenditure management, investment attraction, enhancement of competitiveness, and strategic development directions.